VERBA DENOMINAL DALAM BAHASA INDONESIA - Nurina Ika Sujarwanti; Mukhlish Mukhlish (CARAKA, 2016)
This research aims to describe the process of forming denominal verbs in Indonesian, describe the elements forming denominal verbs in Indonesian, describe the meaning of affixes forming denominal verbs in Indonesian, and describe the function of denominal verb syntactic in Indonesian. This research is descriptive qualitative research. The results of this study are as follows. (1) The process of forming denominal verbs in Indonesian is by affixation, namely prefixation, suffixation konfiksasi, and the combination of affixes. (2) Forming elements in the Indonesian denominal verbs are the origin and the noun prefix ber-, the origin and the noun prefixes meng-, the origin and the noun prefixes di-, the origin and the noun prefixes ter-, the derivative noun and prefixes ber-, the origin and the noun suffix –kan, the origin and the noun suffix –i, the origin and the noun konfiks ke-an, the origin and combination noun affixes meng-kan, and the origin and the nouns affixes meng-kan, the origin and combination noun affixes meng-i. (3) Forming verb affixes meaning denominal in Indonesian is prefix ber- meaning 'having; , wear ', and produce; prefixes meng- meaning, resembling, heading, and do work with the tool; prefix di- meaning 'to do the work with the tool`; prefix ter- with the meaning 'in a state`; suffix –kan  meaning 'make' and `brought into`; suffix –i meaning 'to give or attach`; konfiks ke-an with the meaning of 'hit, suffering or experience`; (h) the combination affix meng-kan  with the meaning of 'doing'; and combination of affix meng-i with the meaning of 'doing'. (4) The function of the syntactic denominal verb in Indonesian is as subject, predicate, and complement.